Sarah Duggan. - DUGGAN, SARAH (Historic New Orleans Collection Quarterly)
The author describes her role as coordinator and research curator at the nonprofit organization Classical Institute of the South. She cites the importance of the free online resource Gulf South Decorative and Fine Arts Database. She also describes the distinctive features of a Greek revival home called Gaineswood located in Demopolis, Alabama.